Analysis of the Factors that Influence the Work Ethic of Bank Muamalat Employees in Palopo City - Muhammad Ikram (Program Studi Perbankan Syariah, IAIN Palopo, 2021)
This research discusses the Influence of Siri’ Religiosity and Culture on the Work Ethic of Employees of Bank Muamalat Kota Palopo. The problem in this study is the work ethic of employees who are less than optimal such as not working in a timely manner, the level of speed and accuracy of work is not good so as to cause problems of low work ethic. This research aims to find out whether siri’ religiosity and culture affect the work ethic of employees of Bank Muamalat Kota Palopo. The type of research used is quantitative methods. The data source used is primary data obtained from the dissemination of questionnaires to respondents, namely employees of Bank Muamalat Kota Palopo. Data is processed and analyzed using multiple linear regression or inferential statistics. The results of this study showed that (1) Thitung religiosity variables amounted to 8,256 and Ttabel by 1,671 or 8,256 > 1,671 and significant value of religiosity of 0.000 <0.05 (H0 was rejected and H1 accepted) Thus it can be interpreted that religiosity has a positive and significant effect on employee work ethic. (2) Thitung culture variables amounted to 6,621 and Ttabel by 1,671 or 6,621 > 1,671 and significant value of Siri’ Culture' (X2) of 0.001 < 0.05 (H0 rejected and H2 accepted). So it can be interpreted that Siri’ Culture (X2) has a positive and significant influence on employee work ethic (Y). (3) Siri’s religiosity and culture simultaneously affect the work ethic of employees of Bank Muamalat Kota Palopo.